Beyoncé and representativeness: analysis of scientific articles on race, gender and other social markers (Simbiótica. Revista Eletrônica, 2025)
The research aims to investigate how the artist Beyoncé has been studied in scientific articles in the Humanities and Applied Social Sciences, considering gender, race and other social markers of difference present in her life trajectory and in her art. The study was carried out through a survey of the multidisciplinary database Scopus, analyzing a total of 41 articles in English. The results revealed that the theme of feminism is the most recurrent, with 11 of the articles retrieved, and that most of the authors are women, which raises questions about the presence of women in academia. Finally, it can be concluded that Beyoncé is a global musical powerhouse and a relevant icon who represents various groups historically neglected by society. Her representativeness broadens relevant discussions and studies, with notes that can help reflect on black people, women and LGBTQIA+, among others.
Keywords: Beyoncé; Representativeness; Social Markers of Difference